2020
DOI: 10.3390/ijms21197136
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of RNA Silencing Suppressor P0 from Pea Mild Chlorosis Virus

Abstract: To counteract host antiviral RNA silencing, plant viruses encode numerous viral suppressors of RNA silencing (VSRs). P0 proteins have been identified as VSRs in many poleroviruses. However, their suppressor function has not been fully characterized. Here, we investigated the function of P0 from pea mild chlorosis virus (PMCV) in the suppression of local and systemic RNA silencing via green fluorescent protein (GFP) co-infiltration assays in wild-type and GFP-transgenic Nicotiana benthamiana (line 16c). Amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 59 publications
(130 reference statements)
1
12
0
Order By: Relevance
“…in PLRV or I225 in PMCV) and W212 (tryptophan or W221 in PLRV or W2256 in PMCV; Han et al, 2010;Sun, Zhuo, et al, 2020;Zhuo et al, 2014).…”
Section: Er-associated Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…in PLRV or I225 in PMCV) and W212 (tryptophan or W221 in PLRV or W2256 in PMCV; Han et al, 2010;Sun, Zhuo, et al, 2020;Zhuo et al, 2014).…”
Section: Er-associated Bodiesmentioning
confidence: 99%
“…However, those motifs are absent from P0, although this protein has a terminal carboxyl sequence (K/R)IYGEDGX3FWR (Figure 1) that could represent a type of novel substrate interaction domain (Pazhouhandeh et al, 2006). Analyses of mutants in this domain of the P0 protein of MABYV, PLRV, and pea mild chlorosis virus (PMCV) have revealed that the suppressor activity is mainly dependent on residues F211 (phenylalanine or F220 in PLRV or I225 in PMCV) and W212 (tryptophan or W221 in PLRV or W2256 in PMCV; Han et al, 2010; Sun, Zhuo, et al, 2020; Zhuo et al, 2014).…”
Section: Characteristics Of Proteins Encoded By Polerovirusesmentioning
confidence: 99%
“…To suppress the host anti-viral RNA silencing, many plant viruses have evolved viral suppressor of RNA silencing (VSR) proteins [ 2 , 3 , 4 , 5 ]. The P0 proteins have been identified as VSR in many poleroviruses, including Turnip yellows virus (TuYV), Cucurbit aphid-borne yellows virus (CABYV), Potato leafroll virus (PLRV), Beet mild yellowing virus (BMYV), Cotton leafroll dwarf virus (CLRDV), Sugarcane yellow leaf virus (ScYLV), Melon aphid-borne yellows virus (MABYV), Maize yellow mosaic virus (MaYMV), Cereal yellow dwarf virus (CYDV), Wheat yellow dwarf virus -GPV isolate (WYDV-GPV), Maize yellow dwarf virus-RMV 2 (MYDV-RMV2), and Pea mild chlorosis virus (PMCV) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The amino acid sequence of P0 proteins throughout the genus shows low identity and the RNA silencing suppressor (RSS) activity of the P0 proteins varies between different viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Different isolates of the same virus (BMYV and PLRV) can exhibit various efficiencies in RSS activity [ 11 , 14 , 22 ]. P0 proteins of several polerovirus members can trigger ARGONAUTE1 degradation via the autophagy pathway to suppress RNA silencing [ 6 , 16 , 23 , 24 ]. Studies have shown that P0 proteins of TuYV, CABYV, CYDV-RPV, CYDV-RPS, and PMCV have a consensus F-box-like domain, through which P0 proteins interact with S-phase kinase-associated protein 1 (SKP1), a component of the SKP1–Cullin F box (SCF) family of the E3 ubiquitin ligases complex [ 10 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation